IN VITRO ASSESSMENT OF EARLY BLIGHT OF TOMATO PATHOGEN WITH FUNGICIDES AND BIOAGENTS (Journal of Plant Disease Sciences, 2025)
Tomato ( Mill.) is one of the most widely grown vegetable crops in the world. However, its production is significantly affected by various diseases, among them Early blight of tomato caused by is most destructive foliar disease. The present study was conducted to evaluate efficacy of different fungicides and bio agents against . Among the fungicides tested Propiconazole 25% EC exhibited complete inhibition of mycelial growth at all concentrations. Combination products such as Tebuconazole + Trifloxystrobin and Carbendazim + Mancozeb also achieved 100% inhibition at the highest concentration. Azoxystrobin + Difenoconazole and Metalaxyl + Mancozeb showed high efficacy with 96.72% and 93.01% inhibition, respectively. Moderate inhibition was recorded with Captan and Mancozeb, while Carbendazim 50% WP alone exhibited comparatively lower efficacy. Among the biocontrol agents evaluated showed the highest efficacy with 73.02% mycelial growth inhibition, followed by and Pseudomonas fluorescens was least effective.
Keywords: Alternaria solani, Bioagents, Early blight, Fungicides